Identify the Big Five Factors of Personality For Knowing Student Interpersonal Communication in Tarakan City Junior High School - Siti Rahmi; Anwar Anwar; Riski Sovayunanto (International Journal of Educational Narratives, 2024)
Background. Interpersonal communication is a process of human activities consisting of two or more people who exchange information, knowledge, thoughts in order to arouse each other's participation. Purpose. herefore, this study aims to determine the identification of Big Five Factors Of Personality to determine the interpersonal communication of junior / senior high school students in Tarakan City.   Method. Survey was applied in this research which data had been analyzed by path analysis after all variables put into a correlational matrix. Results. Through the big five personality theory, there are five dimensions of personality, namely openness (O), conscientiousness (C), extroversion (E), agreeableness (A), neuroticism (N), and can be known to have a significant relationship with interpersonal communication. As the results of research conducted by previous researchers, namely the personality types of extraversion, agreeableness, and oppression have a significant relationship with interpersonal communication. While conscientiousness and neuroticism personality types have no relationship with interpersonal communication. Conclusion. Therefore, this study aims to determine the identification of Big Five Factors Of Personality to determine the interpersonal communication of junior / senior high school students in Tarakan City. Based on the output table on data analysis, it can be seen that the coefficient of determination or R Square is 0.056 or equal to 5.6%, meaning that the variables Opennes to experience, neuroticism, agdreebleness, conscientiousness, extraversion affect interpersonal communication by 5.6%, the rest is influenced by other variables outside the regression equation that are not studied.